2019
DOI: 10.3892/mmr.2019.10399
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GLS1 in intrahepatic cholangiocarcinoma and its clinical significance

Abstract: Kidney-type glutaminase (GLS1) plays a significant role in tumor metabolism. Our recent studies demonstrated that GLS1 was aberrantly expressed in hepatocellular carcinoma (HCC) and facilitated tumor progression. However, the roles of GLS1 in intrahepatic cholangiocarcinoma (ICC) remain largely unknown. Thus, the aim of this study was to evaluate the expression and clinical significance of GLS1 in ICC. For this purpose, combined data from the Oncomine database with those of immunohistochemistry were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Xiang et al demonstrated that GLS1 expression was required for hypoxia-induced migration and invasion in vitro and for tumor growth and metastatic colonization in vivo in CRC cells (64). The important role of GLS1 also shows that the overexpression of GLS1 induced metastasis and invasion and promoted epithelial-mesenchymal transition (EMT) in intrahepatic cholangiocarcinoma (ICC) cells (86). In addition, Li et al demonstrated that targeting GLS1 not only reduced the expression of stemness-related genes including NANOG, OCT4, KLF4, SOX2 and c-Myc, but also suppressed CSC properties via ROS/Wnt/b-catenin signaling (81).…”
Section: Opposite Roles Of Gls1 and Gls2 In Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Xiang et al demonstrated that GLS1 expression was required for hypoxia-induced migration and invasion in vitro and for tumor growth and metastatic colonization in vivo in CRC cells (64). The important role of GLS1 also shows that the overexpression of GLS1 induced metastasis and invasion and promoted epithelial-mesenchymal transition (EMT) in intrahepatic cholangiocarcinoma (ICC) cells (86). In addition, Li et al demonstrated that targeting GLS1 not only reduced the expression of stemness-related genes including NANOG, OCT4, KLF4, SOX2 and c-Myc, but also suppressed CSC properties via ROS/Wnt/b-catenin signaling (81).…”
Section: Opposite Roles Of Gls1 and Gls2 In Tumorigenesismentioning
confidence: 99%
“…By transactivating GLS1 and GOT2 to enhance asparagine synthesis, SOX12 overexpression promotes CRC cell proliferation, migration, invasion, and metastasis (100). GLS1 was also reported to promote cell migration and invasion by regulating EMT in intrahepatic cholangiocarcinoma, in which GLS1 expression was higher in tumor tissues than in peritumoral tissues, and the higher expression of GLS1 independently predicted a poor survival (86). Besides, Ramirez-Peña et al found that experimentally induced EMT breast cancer cells showed a decreased GLS2 expression, which could be further restored by inhibiting the EMT transcription factor FOXC2 (101).…”
Section: Glutaminolysis and Cancer Metastasis: Emt Tumor Immunologymentioning
confidence: 99%
“…1b) and it is thought that these tumor compartments promote GSC enrichment through a mechanism called epithelial-mesenchymal (EMT)-like transition 35 . Concisely, GLS has been reported to regulate the expression of EMT markers in colorectal cancer 36,37 . To assess GLS expression in stem cell-enriched GBM Fig.…”
Section: Gsc In Vitro Models Recapitulate the Glutaminase Expression mentioning
confidence: 99%
“…Several studies reported that increased GLS1 expression was associated with disease aggressiveness and could be used as a prognostic marker in select solid tumors [ 17 , 18 , 19 , 20 ]. However, there is a lack of high-quality studies analyzing GLS1 expression in PCa.…”
Section: Introductionmentioning
confidence: 99%